2010
DOI: 10.1093/humrep/deq217
|View full text |Cite
|
Sign up to set email alerts
|

Does a prediction model for pregnancy of unknown location developed in the UK validate on a US population?

Abstract: A logistic regression model based on two hCG values performed with modest decreases in predictive ability in a US cohort for women at risk for EP compared with the original UK population. However, the sensitivity for EP was too low for the model to be used in clinical practice in its present form. Our data illustrate the difficulties of applying algorithms from one center to another, where the definitions of pathology may differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 19 publications
0
39
1
Order By: Relevance
“…Both these factors would add to the calculated risk of EP by protocol M4. Interestingly, contrary to EPs in our cohort and a UK population, the hCG levels were twice as high as compared with a US population where the M4 model was evaluated (Barnhart et al, 2010) and only identified 49% of the EPs.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Both these factors would add to the calculated risk of EP by protocol M4. Interestingly, contrary to EPs in our cohort and a UK population, the hCG levels were twice as high as compared with a US population where the M4 model was evaluated (Barnhart et al, 2010) and only identified 49% of the EPs.…”
Section: Discussioncontrasting
confidence: 83%
“…This limitation together with the study's retrospective nature emphasises the need of prospective studies. The use of estimated 48 h hCG values in the present study could also ultimately have had an impact on the performance of the protocols, although the original curves for a viable IUP were derived from the use of log lineartransformed hCG values and have subsequently been used in other studies (Barnhart et al, 2004(Barnhart et al, , 2010Zee et al, 2013). Strengths of the study are the relatively large sample size with a high prevalence of EPs, and the setting that reflected real clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prediction models may lose excellent test characteristics when applied externally, or may need to be amended or updated to maintain accuracy (20). The purpose of this study is to compare observed hCG curves to expected curves in a diverse set of patients with symptomatic early pregnancy and a PUL in order to predict outcome.…”
Section: Introductionmentioning
confidence: 99%